Oxidative stress mediated electrolyte imbalance in 30 known cases of knee osteoarthritis patients: A clinical approach - Dutta, Jusmita; Sharma, Dilutpal; Saxena, Rahul (Asian Journal of Medical Sciences, 2015)
Background: Osteoarthritis (OA), also known as degenerative arthritis, is the leading cause of chronic disability in elderly. Although, it is a process of progressive deterioration of articular cartilage with ageing which involves numerous risk factors, it is conceivable that oxidative stress mediated electrolyte imbalance may have a crucial role in the development of hypertension risk in OA elderly. Aims & objective: The present study was designed to assess the association of oxidative stress and altered serum electrolyte levels in OA elderly patients and to determine their effect in predicting hypertension (HT) risk. Methods: Total antioxidant activity (TAA), lipid peroxidation (malondialdehyde; MDA) and serum mineral (Na+, K+, Mg2+ and Ca2+) levels were estimated in 40 OA elderly patients by using standard methods and statistically compared it with that of 40 healthy normal individuals of same age group (55-70 years). Result: Plasma TAA, serum potassium, magnesium and calcium levels were significantly low in patient group (p<0.05) as compared to healthy controls whereas erythrocyte MDA levels were significantly high in OA subjects. However, serum sodium levels were increased insignificantly (p<0.1) in OA subjects. Conclusion: Our findings indicate that oxidative stress plays a significant role in shaping the OA older population to develop future hypertension, characterized by altered serum minerals levels. Therefore, consumption of diet rich in antioxidants, proteins and minerals with low dietary salt should be increased with senescence in order to prevent disease complexity. DOI: http://dx.doi.org/10.3126/ajms.v6i5.12274 Asian Journal of Medical Sciences Vol.6(5) 2015 26-30